Engagement in computerized cognitive training instructions by older people. A within-subject design to evaluate comprehension and acceptability of serious games instructions - Nahas, Christelle; Gandit, Marc; Monfort, Emmanuel (Frontiers in Aging, 2025)
This article emphasizes the advantages of using a within-subject experimental design to assess the impact of salient visual cues on the comprehension and acceptability of computerized cognitive training (CCT) instructions among older adults. The study would involve participants aged 65 and above, who will engage in an online experiment presenting two sets of instructions for serious games: one with salient visual cues and one without. This within-subject design eliminates the need for random assignment, improves internal consistency, and enhances statistical power. Participants serve as their own controls, providing a more robust comparison of how visual cues affect instruction comprehension and software acceptance. The primary objective is to identify indicators of acceptability for CCT serious games and to evaluate how well participants comprehend the instructions, influencing their intention to use the software. The hypothesis suggests that salient visual cues will improve instruction comprehension and foster greater software acceptability. By focusing on this design method, the study aims to enhance the engagement of older adults in cognitive training programs, reducing dropout rates. This research offers valuable insights into methodological strengths that can be applied in future studies to improve the usability and acceptance of CCT tools for older adults without cognitive impairments.